ISSUES OF EARLY DETECTION AND COMPREHENSIVE MANAGEMENT OF GASTROESOPHAGEAL REFLUX DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Gastroesophageal reflux disease (GERD) is one of the most common chronic disorders of the digestive system, developing as a result of the pathological reflux of gastric contents into the esophagus. The clinical significance of this disease is determined not only by its high prevalence, but also by its substantial negative impact on patients’ quality of life, as well as its potential to lead to serious complications such as esophagitis, peptic stricture, Barrett’s esophagus, and adenocarcinoma. Early detection of GERD plays an important role in slowing disease progression, reducing the risk of complications, and selecting an individualized treatment strategy. This article provides a scientific analysis of the etiology and pathogenesis of GERD, the criteria for early diagnosis, its clinical and subclinical forms, modern diagnostic methods, and the principles of comprehensive management. In addition, the roles of lifestyle modification, pharmacotherapy, and endoscopic and surgical approaches are discussed.